EMOTION RECOGNITION IN LEARNERS WITH EMOJI SENTIMENT ACCOMPANIMENT USING THE PHOBERT MODEL - Thi Dung, Tran; Nhat Tung, Le; Ngoc Dung, Bui; Huan, Vu (HNUE Journal of Science: Journal of Natural Sciences, 2024)
This paper proposes an advanced method for recognizing learners' emotions by incorporating the use of emojis to reflect the modern communication tendencies of learners, typically young individuals. The method is built on the PhoBERT model, a variant of BERT optimized for Vietnamese. Data was collected from opinion surveys of learners at the Ho Chi Minh City campus of the University of Transport and Communications to train and test the model. The system is designed to analyze text and recognize seven basic emotions: enjoyment, trust, hope, sadness, surprise, fear, and others. Corresponding emojis are then assigned to each emotion type to more clearly illustrate the learners' emotional states. Experimental results show that combining PhoBERT and emojis not only enhances the accuracy of emotion recognition but also makes communication more intuitive and vivid. The model achieved an accuracy of 74.1%. The paper also discusses practical applications of this system in the field of education, where teachers can quickly and accurately understand and respond to students' emotions, thereby improving teaching effectiveness.